Information technology, business sustainability and female economic participation in Sub-Saharan Africa - Simplice Asongu; Mushfiqur Rahman; Mohammad Alghababsheh (African Governance and Development Institute (AGDI), 2022)
This study assesses how business/financial sustainability in the perspective of financial stability moderates information technology to influence female economic participation in 49 countries in Sub-Saharan Africa for the period 2008-2018. The empirical evidence is based on Tobit regressions that enabled the study to account for the censored nature of the outcome variables. The following important findings are established. First, ICT dynamics (mobile phone penetration, internet penetration and fixed broadband subscriptions) are consistently moderated by business sustainability to positively affect female employment in the industry. Second, business sustainability scores need to exceed certain thresholds before moderating fixed broadband subscriptions to induce favorable overall effects on female employment, female labour force participation and female unemployment rates. These thresholds are 18.742 and 19.505 Z-scores for positive effects on female employment and female labour force participation, respectively and a Z-score of 17.300 for a negative impact on female unemployment. The thresholds which should be exceeded are within policy reach, make economic sense and are policy relevant. The study contributes to the extant literature by providing actionable thresholds of business sustainability that can be employed by policy makers in order for information technology to positively influence female economic inclusion in Sub-Saharan Africa.
Keywords: E23; F21; F30; L96; O55; 330; information technology; business sustainability; gender inclusion